2019
DOI: 10.1128/msystems.00242-18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome Analysis of an Extensively Drug-Resistant Isolate of Avian Sequence Type 167 Escherichia coli Strain Sanji with Novel In Silico Serotype O89b:H9

Abstract: Extensive drug resistance (XDR) is an escalating global problem. Escherichia coli strain Sanji was isolated from an outbreak of pheasant colibacillosis in Fujian province, China, in 2011. This strain has XDR properties, exhibiting sensitivity to carbapenems but no other classes of known antibiotics. Whole-genome sequencing revealed a total of 32 known antibiotic resistance genes, many associated with insertion sequence 26 (IS26) elements. These were found on the Sanji chromosome and 2 of its 6 plasmids, pSJ_25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 81 publications
(77 reference statements)
3
12
0
Order By: Relevance
“…Moreover, the O antigen gene cluster, O89 was found to be present in all ST167 E. coli strains as recently reported (37). The co-occurrence of the bla NDM-5 gene in serotype O89 harboring ST167 clone with fitness and virulence factors such the capsule synthesis clusters could explain its global dissemination as a high-risk clone.…”
Section: Ndm-encodingsupporting
confidence: 76%
“…Moreover, the O antigen gene cluster, O89 was found to be present in all ST167 E. coli strains as recently reported (37). The co-occurrence of the bla NDM-5 gene in serotype O89 harboring ST167 clone with fitness and virulence factors such the capsule synthesis clusters could explain its global dissemination as a high-risk clone.…”
Section: Ndm-encodingsupporting
confidence: 76%
“…In a previously performed genomic analysis of ST167 strains, it was hypothesized that ST167 and its related ST617 lineage emerged from clone ST10 by the complete loss of the wca operon, encoding colanic acid biosynthesis in the lipopolysaccharide (LPS) biosynthesis pathway (12). Furthermore, a recent study proposed the O89b name for the novel variant of O89 antigen identified in ST167 detected in all strains of the clone (9). Both studies evidenced that the ST167 lineage has peculiar virulence and surface antigen features that could justify its worldwide spread as a high-risk clone.…”
Section: Discussionmentioning
confidence: 99%
“…Community sources for the OXA-244-producing E. coli isolates seem possible since many of the patients had not been hospitalised and the E. coli isolates belonged to STs that are present in the community [23][24][25][26][27][28][29][30][31][32]. The ECDC RRA identified one main geographically dispersed ST38 OXA-244-producing E. coli cluster with chromosomal-encoded bla OXA-244 present in all 10 countries, including Denmark, that submitted data for the RRA [10].…”
Section: Discussionmentioning
confidence: 99%